Diversity of the gut, vaginal and oral microbiome among pregnant women in South Africa with and without pre-eclampsia - Geldenhuys, Janri; Redelinghuys, Mathys J.; Lombaard, Hendrik A.; Ehlers, Marthie M.; Cowan, Don; Kock, Marleen M. (Frontiers in Global Women's Health, 2022)
Background: Changes in microbial communities are a known characteristic of various inflammatory diseases and have been linked to adverse pregnancy outcomes, such as preterm birth. However, there is a paucity of information regarding the taxonomic composition and/or diversity of microbial communities in pre-eclampsia. The aim of this study was to determine the diversity of the gut, vaginal and oral microbiome in a cohort of South African pregnant women with and without pre-eclampsia. The diversity of the gut, vaginal and oral microbiome was determined by targeted next generation sequencing (NGS) of the V3 and V4 region of the 16S rRNA gene on the Illumina MiSeq platform. Results: In this study population, pre-eclampsia was associated with a significantly higher alpha diversity (P = 0.0472) in the vaginal microbiome accompanied with a significant reduction in Lactobacillus spp. (P = 0.0275), compared to normotensive pregnant women. Lactobacillus iners was identified as the predominant species of the vaginal microbiome in both cohorts. High inter-individual variation in alpha diversity was observed in the gut and oral microbiome in both cohorts. Although differences in the relative abundance of bacteria at all phylogenetic levels were observed, overall microbial composition of the gut, oral and vaginal microbiome was not significantly different in the pre-eclampsia cohort compared to the normotensive cohort. Conclusion: Collectively, a reduction of Lactobacillus spp., and predominance of L. iners in pregnant women with pre-eclampsia could suggest an unstable vaginal microbiome that might predispose pregnant women to develop pregnancy complications. The lack of significant structural changes in the gut, oral and vaginal microbiome does not suggest that the characterized communities play a role in pre-eclampsia, but could indicate a characteristic unique to the study population. The current study provided novel information on the diversity of the gut, oral and vaginal microbiome among pregnant women in South Africa with and without pre-eclampsia. The current study provides a baseline for further investigations on the potential role of microbial communities in pre-eclampsia.